KNOWLEDGE SHARING AND CREATIVITY VALUE AS AN EFFORT TO IMPROVE ISLAMIC BANKING PERFORMANCE - Ummi Syakinah, Innani; Abadiyah, Rifdah; Adji Kusuma, Kumara (JURNAL EKBIS, 2024)
When employee needs are met at work, job satisfaction will arise. Where job satisfaction is a state of happy emotions or positive emotions that come from an assessment of one's work or experience. With high job satisfaction, it will improve employee performance towards the organization where they work. Performance is the result of an employee's actions in carrying out the role given by the organization, both quantity and quality in accordance with the responsibilities given. For the Islamic banking industry, knowledge sharing is very important because it allows staff members to exchange knowledge, skills and experiences. By sharing ideas and knowledge the Islamic banking sector can stimulate innovation in its products and services that comply with sharia principles. This can help the banking sector to remain relevant and compete in the growing Islamic finance market. This study aims to determine the mediating role of job satisfaction on employee performance which is influenced by knowledge sharing and creativity value. This research is a quantitative study with SEM-PLS as a data analysis method with the Smart PLS 3.0 tool. Consists of 50 research sample respondents. The results showed that knowledge sharing, creativity value, and job satisfaction have a positive and significant influence on employee performance. Furthermore, knowledge sharing and creativity value have a positive and significant influence on employee performance of BSI Bank KCP Sidoarjo employees through job satisfaction.